2016
DOI: 10.1186/s12913-016-1393-7
|View full text |Cite
|
Sign up to set email alerts
|

Medicine and management: looking inside the box of changing hospital governance

Abstract: BackgroundHealth policy has strengthened the demand for coordination between clinicians and managers and introduced new medical manager roles in hospitals to better connect medicine and management. These developments have created a scholarly debate of concepts and an increasing ‘hybridization’ of tasks and roles, yet the organizational effects are not well researched. This research introduces a multi-level governance approach and aims to explore the organizational needs of doctors using Sweden as a case study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…In addition, considering high turnover of executive leadership, healthcare organisations often rely on external talent for succession management which can reduce hospital efficiency [44, 66]. Other contributors to weakened hospital performance include: the lack of allocative efficiency and transparency [24, 30, 64, 67]; poor hospital processes that hamper the development of effective systems for the prevention and control of hospital acquired infections (HAIs) [53, 68]; and, payment reforms such as value-based funding and fee-for-service that encourage volume [18, 23, 24, 61, 62, 69, 70].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, considering high turnover of executive leadership, healthcare organisations often rely on external talent for succession management which can reduce hospital efficiency [44, 66]. Other contributors to weakened hospital performance include: the lack of allocative efficiency and transparency [24, 30, 64, 67]; poor hospital processes that hamper the development of effective systems for the prevention and control of hospital acquired infections (HAIs) [53, 68]; and, payment reforms such as value-based funding and fee-for-service that encourage volume [18, 23, 24, 61, 62, 69, 70].…”
Section: Resultsmentioning
confidence: 99%
“…The nature of the medical management function differed. In some studies, these positions were full-time affiliations in which the physicians ceased to perform clinical work [ 34 ], whereas in other cases, the positions were considered as a part-time jobs ‘on the side’, meaning that they will first and foremost be a physician [ 6 ], and finally, there were studies in which both full- and part-time variants were identified [ 31 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, physicians must gain support and trust from the management world to obtain authority and responsibility and prevent exclusion from key decisions and strategy. In conclusion, support and trust form an important component of a medical manager’s power base [ 35 ] and are needed not only to become effective but also to prevent stress and working in isolation [ 41 ]. Paradoxical, a few authors [ 51 , 54 ] mentioned that in some cases, physicians explicitly did not want support because sharing their problems could lead to public failure and the loss of credibility and status.…”
Section: Resultsmentioning
confidence: 99%
“…Empirical research has found that doctors with management roles may be isolated 'lone wolves' and lack organizational support. 8 It is therefore important for doctors to receive appropriate training and support for additional roles.…”
Section: Interpretation Of Findings In Context Of Wider Literaturementioning
confidence: 99%